Penggunaan Media Belajar Pop-Up Book dalam Pembelajaran Tematik serta Pengaruhnya Terhadap Motivasi Belajar dan Hasil Belajar - Siti Khasanah Maisaroh; Nina Kumalasari; Rizqina Anjarwati; Elisa Novita Fiky Megantari; Muhammad Arif Sukahar; Taufik Muhtarom (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Thematic learning in elementary schools often faces challenges such as monotony, lack of media variation, and low student motivation. This study aims to determine the effectiveness of using pop-up book devices in theme-based learning and the impact of pop-up book devices on student achievement or learning outcomes in theme-based learning. The technique used in this study is Systematic Literature Review. In the search, a total of 4,700 scientific papers were found from 2015 to 2025, which were progressively and systematically selected down to 15 relevant scientific papers concerning the use of pop-up book learning media in theme-based learning and its influence on motivation and learning outcomes. The results and findings in the scientific paper indicate that the pop-up book device is proven to be effective in the thematic learning process at the elementary school level due to its attractive, interactive, and contextual nature. It encourages students' learning motivation both intrinsically and extrinsically, marked by increased active participation, curiosity, and student involvement in learning. The improvement in students' learning achievements after utilizing the pop-up book device includes cognitive aspects (understanding of the material), affective aspects (positive attitudes towards learning), and psychomotor aspects (creative and collaborative skills).